Combination of functions

You will be asked to combine functions. In this tutorial you are shown what we mean by combining functions and introduced to a simple example and the notation that you may expect to see.


Examples in the video

\text{If}\hphantom{aa}f(x) = 2x - 3,\hphantom{aa} g(x) = \dfrac{3}{x},\hphantom{aa} x \ne 0{\hphantom{aa}\text{and}\hphantom{aa}}h(x) = {x^2}


  1. fg(x)
  2. gfh(x)
  3. fff(x)


Example 2

Examples in the video

\text{If}\hphantom{aa}f(x) = {e^{2x + 1}},\hphantom{aa} g(x) = 2x - 4\hphantom{aa}\text{and}\hphantom{aa}}h(x) = \ln x


  1.     \[fg(x)\]

  2.     \[hf(x)\]

  3.     \[fh(x)\]

This website uses cookies and third party services. Settings Ok